KENDALA GURU DALAM PELAKSANAAN PENILAIAN PORTOFOLIO PADA KURIKULUM 2013 DI SEKOLAH DASAR - Romadhon, Nur Latif Gita; Irianto, Sony; Anggoro, Subuh (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This research is a descriptive qualitative study that aims to describe the rules discussed by teachers in the 2013 curriculum assessment portfolio in elementary schools. This research is a qualitative descriptive type. Data collection techniques used are interviews, observation, and documentation. The research subjects were fourth grade teachers in three elementary schools namely Karangsalam Elementary School, 1 Beji Elementary School, and Karangnangka Public Elementary School. The data analysis technique used is descriptive qualitative which consists of data reduction, displaying data, and completing conclusions. The validity test of the data used is by the tirangulasi technique that compares the results of observations, interviews, and documentation. The results of the study show that: 1) the evaluation time or portfolio process is quite long; 2) contribution of aspects that must be approved; 3) student activity that is still low; 4) there are still outdated students with the learning given by the teacher